Hashimoto Thyroiditis, Anti-Parietal Cell Antibodies: Associations With Autoimmune Diseases and Malignancies - Boutzios, Georgios; Koukoulioti, Eleni; Goules, Andreas V.; Kalliakmanis, Ioannis; Giovannopoulos, Ilias; Vlachoyiannopoulos, Panayiotis; Moutsopoulos, Haralampos M.; Tzioufas, Athanasios G. (Frontiers in Endocrinology, 2022)
Background: Hashimoto thyroiditis (HT) is an autoimmune disease which may result in extensive damage of the thyroid gland. Chronic atrophic gastritis (CAG), is the most frequent HT-associated disorder, with anti-parietal cell autoantibodies (APCA) being a screening test for autoimmune CAG. The aim of this study was to investigate, in a cohort of HT patients: a) the prevalence of APCA in an attempt to define their clinical phenotype and b) any possible associations of APCA with other autoimmune diseases and malignancies. Methods: This is a single-center, case-control study, conducted at a University Hospital. The study included patients with HT diagnosed between November 2017 and November 2020. Excluded were patients <18 years old, with sonographic features of HT but negative thyroid peroxidase (TPOAbs) or thyroglobulin autoantibodies (TgAbs), Graves’ disease, Down or Turner's syndrome. Results: 840 patients with HT were included in the study, from whom 180 (21.4%) had positive APCA. 79 patients (9.4%) had one or more organ-specific autoimmune diseases and 61 (7.3%) had a systemic autoimmune disease. Autoimmune diseases were more frequent in female than in male patients (17.9% versus 10.9%, p=0.05). APCA-positive patients were older than APCA-negative (54.1±13.5 versus 49.0±14.6, p<0.001) and had more often positive TPOAbs (93.3% versus 83.9%, p=0.001). Gastric neoplasms were documented only in APCA-positive patients (p<0.001). A higher frequency of organ-specific autoimmune diseases was observed in the APCA-positive group (14.4% versus 8%, p=0.024). In the subgroup of patients with additional autoimmune diseases (n=140), younger age and positive APCA were independently associated with the presence of organ-specific autoimmunity (OR 0.954, 95% CI 0.927-0.982 and OR 3.100, 95% CI 1.256-7.652, respectively). Papillary thyroid cancer (PTC) occurred in 3.5% of patients (26/29 females). Positive family history for thyroid autoimmunity and negative TPOAbs were the only independent risk factors for PTC among women (OR 3.228, 95% CI 1.173-8.887 and 0.315, 95% 0.113-0.881, respectively). Conclusion: This study reveals for the first time an association of APCA with organ-specific autoimmunity in HT patients. APCA together with patient age were independently associated with the presence of organ-specific autoimmunity. Finally, this study showed an association between APCA and gastric neoplasms in these patients.